EFFECTS OF CREDIT RISK MITIGATION STRATEGIES ON PROFITABILITY OF MICROFINANCE INSTITUTIONS IN NAKURU TOWN - MAINGI, KARIUKI JOSEPH (KABARAK UNIVERSITY, 2017)
Credit risk is on an increasing rate and is becoming an area of concern to many people and institutions in the lending business globally. This kind of exposure leads to instability and poor financial performance of microfinance institutions. Microfinance institutions are exposed to credit risk and therefore it is important for them to come up with mitigation strategies. The current study sought to find out the effects of credit risk mitigation strategies on the profitability of microfinance institutions in Nakuru town. The objectives of the study were to determine the role of loan appraisal procedures, debt recovery policies, credit risk monitoring and diversification of credit products on the profitability of microfinance institutions in Nakuru town. The study used a sample size of 75 respondents who were drawn from selected microfinance institutions in Nakuru town. The target population for the study was 500 respondents drawn from various microfinance institutions in Nakuru town. The sample size comprised of respondents drawn from various microfinance institutions drawn in Nakuru.Questionnaires were the main data collection tool that was used. Data was analyzed using the Statistical Package for Social Sciences (SPSS) and was presented in form of frequency tables, charts and graphs. The results revealed that credit risk monitoring was negatively correlated with profitability. However, this correlation was not statistically significant hence the null hypothesis 3 was retained and concluded that there was no evidence based on the sample to suggest that credit risk monitoring as associated with profitability. This is in agreement of the findings from a study carried out by Saunders, (2012) in the United States, the findings indicated that debt recovery policies largely affected the profitability of microfinance institutions. He looked at various microfinance institutions in the country and also investigated the policies that were being used in debt collection. The results revealed that credit risk monitoring was negatively correlated with profitability. The results revealed that credit risk monitoring was negatively correlated with profitability.
FULL TEXT
Keywords: Credit Risk, Debt Recovery, Diversification, Loan appraisal